Village Midline Study: Vaishali, Bihar State, India - Jagannath, Pratyaya; Kargwal, Kanchan; Sharma, Namrata; Prasad, Sanjay; Nagpal, Mansi; Khatri-Chhetri, Arun (2020)
This report summarizes the findings of the village midline study (VMS) conducted in Mukundpur village at the CCAFS benchmark site of Vaishali district, India. The VMS was conducted between June 5th to 8th 2019 to complement an earlier household midline survey and the village baseline survey done in the same district. The village midline study aims to document changes reported since the village baseline study on some fundamental indicators of natural resource use, organizational landscapes, weather and agriculture-related information networks, as well as information on mitigation of climate change’s negative effects. The survey used participatory methods of data collection in which the community’s men and women respondents worked separately, thus forming two separate data collection groups. During the midline study, the men’s and women’s groups identified 14 organizations supporting agriculture, livestock, Micro Finance Institution (MFI), education, food distribution, and community development. The participants also reported issues of corruption, irregular service, performance dissatisfaction, and unequal allocations of resources. The main focus of the food security-related organizations reported are on dairy production and marketing, access to inputs, crop production, food distribution, and weather-based crop insurance. There is virtually no permanent institution working solely on food security, however those identified, support aspects of food security, such as ensuring food availability for households. No organizations are working specifically in natural resources management (NRM) other than those working in livestock and agriculture. NRM related activities of the organizations identified include the provision of inputs, training, and tree saplings in addition to climate change education via a Climate-Smart Village program. Furthermore, the men’s and women’s groups identified numerous sources for information on weather, agricultural production, markets, seeds, fertilizers, and pesticides. A total of 8 information sources were reported. Among those, the most popular source of information remain friends and relatives, followed by neighbours and observation. Even though the village’s population is facing significant crops and dairy production constraints, very few information sources were noted for the agricultural sector and in particular, no information source was reported for livestock. Finally, the recommendations from the two groups focus on addressing water access and availability, improving crop and dairy productivity, and mitigating climate change impacts to maintain their food security and livelihoods. In summary, Mukundpur village requires improved access to knowledge and resources with more regular, targeted, equitable and timely assistance from local organizations that directly address the area’s food security and natural resource management related dynamics.